DIVERSI DALAM PENYELESAIAN KASUS NARKOBA YANG MELIBATKAN ANAK YANG BERKONFLIK DENGAN HUKUM - Machbuby, Achmad Eric; Soekorini, Noenik; Aranggraeni, Renda (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The high number of narcotics crimes involving minors has created a dilemma between law enforcement and child protection. The problem addressed in this study is how diversion is applied in the settlement of child drug cases and the challenges faced in its implementation. This study uses a normative juridical method with a legislative and conceptual approach. The results show that although the RJ approach has been accommodated in the juvenile justice system in Indonesia through Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, its implementation in drug cases still faces many obstacles. These obstacles include a lack of understanding of RJ principles among law enforcement officials, resistance from the community, and the absence of clear technical guidelines on the application of RJ to narcotics cases. In addition, the repressive nature of narcotics laws poses a normative obstacle to harmonizing the approaches of criminal punishment and restorative justice. This study recommends the synchronization of regulations and the improvement of legal resources so that the implementation of RJ for children involved in drug cases can be carried out optimally